Transcutaneous tibial nerve stimulation: A promising non-invasive treatment for chronic anal fissure: Systematic review article - Elnibras, Mohammed; Barnawi, Haneen; Shawir, Mohamad (Edelweiss Applied Science and Technology, 2025)
Anal fissure is a linear tear in the anoderm located just below the dentate line. It is a prevalent anorectal condition that affects both men and women, with an incidence rate of 1 in 350 people. The primary symptom is severe, distressing post-defecation pain, along with bright red rectal bleeding and pruritus ani. The pain has a significant negative impact on the quality of life of affected patients. Chemical sphincterotomy using topical nitrates, botulinum, calcium channel blockers, and surgical sphincterotomy using left lateral internal sphincterotomy have been a mainstay of managing chronic anal fissure for decades. However, in recent years, neuromodulation using sacral or tibial nerve stimulation has emerged as an alternative non-invasive management. The aim of this study is to assess the effect of transcutaneous tibial nerve stimulation in managing anal fissures. The primary outcome is the healing rate, and the secondary outcome is the complication rate. Google Scholar, PubMed, and Web of Science are systematically searched for relevant and similar articles, using transcutaneous tibial nerve stimulation AND anal fissure as keywords. The pooled data analysis revealed that the healing rate of chronic anal fissures using transcutaneous tibial nerve stimulation is 69.6%, with a complication rate of 0%. Transcutaneous tibial nerve stimulation is an effective non-invasive method to treat chronic anal fissures, with no complications and a promising success rate, which may be useful to patients at high risk for fecal incontinence or who do not wish to undergo surgery.